2007
DOI: 10.1002/pon.1174
|View full text |Cite
|
Sign up to set email alerts
|

Supportive care of rural women with breast cancer in Tasmania, Australia: changing needs over time

Abstract: Providing for patients' psychosocial needs is a potential means of minimising cancer morbidity. Needs assessments can guide responsive patient-centred care. A longitudinal survey of women with early breast cancer consulting a breast nurse in a primarily rural state of Australia was undertaken to measure unmet supportive care needs, identify changes in unmet needs across time and compare results with previous studies. Needs assessments were completed with the Supportive Care Needs Survey (SCNS) at 1 month (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
4
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 45 publications
6
52
4
1
Order By: Relevance
“…This result is not surprising given the nature of this patient population's prognosis. The results are similar to those in literature using the Supportive Care Needs Survey, examining, in general, the needs of cancer patients, those with brain tumours, those with melanoma and those with breast cancer (Bonevski et al, 1999;Sanson-Fisher et al, 2000;Janda et al, 2008;Minstrell et al, 2008).…”
Section: The Needs Of Patients With Advanced Incurable Cancersupporting
confidence: 77%
“…This result is not surprising given the nature of this patient population's prognosis. The results are similar to those in literature using the Supportive Care Needs Survey, examining, in general, the needs of cancer patients, those with brain tumours, those with melanoma and those with breast cancer (Bonevski et al, 1999;Sanson-Fisher et al, 2000;Janda et al, 2008;Minstrell et al, 2008).…”
Section: The Needs Of Patients With Advanced Incurable Cancersupporting
confidence: 77%
“…The possibility for bias in the recruitment process was noted in many studies [e.g. 35,40]. Almost all the studies (including population based studies with a control group) used a cross sectional design, leading to a lack of measurement of long term outcomes and an inability to explore causality.…”
Section: Qualititative Studies Without Control Groupsmentioning
confidence: 99%
“…The single longitudinal study, with a sample of 89 Australian women with breast cancer [35], reported that most needs decreased significantly between 1 and 3 months post diagnosis, although sexuality needs increased over this timeframe. The most common reported needs at one month post diagnosis were psychological: worries for those closest to you, fears about the cancer spreading, fears about the cancer returning and anxiety about having treatment.…”
Section: Quantitative Studies With No Control Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, those requiring more intensive treatment and those diagnosed at a more advanced stage are also known to report greater need, with further variance observed across time from diagnosis to follow-up care [11].…”
Section: Introductionmentioning
confidence: 99%